2009
DOI: 10.1016/j.jcrs.2008.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Visual performance and contrast sensitivity after phacoemulsification with implantation of aspheric foldable intraocular lenses

Abstract: All 3 aspheric IOLs significantly decreased positive spherical ocular aberration after phacoemulsification and may induce negative spherical aberration. However, there was no significant difference in total higher-order RMS values between the IOLs. The 3 IOL models provided comparable contrast sensitivity and visual performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
3
15
0
1
Order By: Relevance
“…In fact, the differences in asphericity of IOLs do not lead to different study results. Two RCTs 60,61 found no difference in the contrast sensitivity measurements after the implantation of different aspheric IOLs, whereas another study did demonstrate a significant difference. 62 Several authors have proposed IOL selection according to the degree of corneal spherical aberration.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, the differences in asphericity of IOLs do not lead to different study results. Two RCTs 60,61 found no difference in the contrast sensitivity measurements after the implantation of different aspheric IOLs, whereas another study did demonstrate a significant difference. 62 Several authors have proposed IOL selection according to the degree of corneal spherical aberration.…”
Section: Discussionmentioning
confidence: 93%
“…A comparative study of 3 aspheric IOLs showed no significant difference in wavefront analysis, contrast sensitivity, or highcontrast visual acuity. 35 In the latter study, higherorder aberrations (HOAs) were measured with the pupils dilated using an Optical Path Difference scan device (ARK 10000 OPD, Nidek Co. Ltd.); a central pupil diameter of 4.0 mm, 5.0 mm, and 6.0 mm was selected for each eye. In another study, 36 the Akreos Adapt AO IOL and the Tecnis Z9000 IOL gave similar photopic and mesopic contrast sensitivity; the HOAs, especially spherical aberration, were lower with the Tecnis Z9000 IOL; however, the Akreos AO IOL provided a greater depth of field and higher perceived visual quality.…”
Section: Discussionmentioning
confidence: 99%
“…Like previous studies we used aberrometric analysis as a determinant of postoperative visual function. 1 , 2 , 3 , 6 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 Santiago and associates 3 in their study found that eyes implanted with the aspherical IOL Akreos AO showed lower values of spherical aberration and improved contrast sensitivity compared with eyes implanted with the spherical IOL Akreos Fit. By comparing HoRMS, total RMS and Z4 between two eyes (for 5 and 6 mm pupil), we found no significant difference between two lenses, but these factors were decreased 3 months postoperatively in comparison with 1 month postoperatively, which were in relation with postoperative BCVA and contrast sensitivity.…”
Section: Discussionmentioning
confidence: 94%